Komunitas Belajar dalam Lesson study untuk Memberdayakan Kognitif dan Psikomotor Siswa pada Pembelajaran Biologi di Luar Kelas - Zukmadini, Alif Yanuar; Lestari, Puji; Rochman, Syaiful; Karyadi, Bhakti (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to enhance cognitive and psychomotor abilities through outdoor learning, designed and evaluated collaboratively by the learning community within the framework of the Lesson study. The study was conducted on grade X students of MAN Insan Cendekia Bengkulu Tengah. Lesson study was carried out in two cycles, each consisting of the plan, do, and see stages. The "plan" stage is the planning stage to prepare the learning tools and strategies that will be carried out. The "do" stage is the implementation of the learning that has been designed. The "see" stage is a reflection of the learning activities that have been carried out. The instruments used consist of observation sheets and test paper. Data is analyzed by calculating the average percentage of each observation indicator, while cognitive and psychomotor learning outcomes are analyzed by calculating the average value obtained. Implementation of the lesson study achieved a percentage score of 100%. Cognitive learning outcomes from cycle I to cycle II increased by 20.43%. Meanwhile, psychomotor learning outcomes increased by 26.79%. The ecosystem acts as a direct learning context that does not only present objects of study to be studied but can also facilitate students to develop conceptual understanding and scientific skills simultaneously. Thus, the reflection carried out will encourage teachers to make continuous improvements. The conclusion of this study is that lesson study activities involving the role of the learning community can improve the planning, implementation, and reflection of biology learning outside the classroom, thus having a significant impact on improving students' cognitive and psychomotor learning outcomes.